Preparation and characterization of polyethersulfone hollow fiber nanofiltration membranes made from PES/NMP/PEG 400/WATER - Jalil, Suhana; Ismail, Ahmad Fauzi; Hashim, Shahrir (2004)
The objective of this study is to develop nanofiltration hollow fiber membrane from a sophisticated multi component spinning dope. Polyethersulfone (PES) asymmetric nanofiltration (NF) hollow fibers membranes were prepared by a simple dry/wet phase inversion process from spinning solution consisted of N-Methyl-2-Pyrrolidone (NMP), Polyethylene-glycol (PEG 400) as polymeric additive and pure water as a non-solvent additive. These fibers have been produced from a newly developed spinning solution with a mass ratio of 21.34/31.22/10.2/7.24 (PES/NMP/PEG/water). The dope formulation was designed to be very close to its cloud point (binodal line) in order to speed up the coagulation of the nascent fibers so that the relaxation effect on molecular orientation is reduced. Sodium chloride solution was used to determine the rejection rate of the membranes. In order to achieve high performance NF membranes, the effects of shear rate on the separation performance of NF hollow fiber membrane were studied. Thus, different dope extrusion rate (DER) ranging from 2.0 to 3.5 cm3/min were used to produce the fibers. The results are used to correlate the relationship between DER and the separation performance (rejection) of the membrane. Experimental results show a significant effect of extrusion shear on the rejection rate of the membranes. As the shear rate was increased, the rejection increased until a certain level, before the rejection decreases. Finally, the optimum shear rate was observed in this study and it was about 2.5 cm3/min. In conclusion, we demonstrated that increasing the shear rate (DER) experienced by the spinning solution during membrane fabrication increased the molecular orientation and this had favorable effect on membrane rejection.